Some operations of electric power supply system in Benin City area of Nigeria (2010)
The Power Holding Company of Nigeria (PHCN) is responsible for generating, transmitting, distributing and selling electric power to the various consumers throughout the country. The paper presents the results of an investigation conducted on some of the operations of Power Holding Company of Nigeria (PHCN) to determine some of the major factors affecting the availability of power supply to consumers in Benin City area of Nigeria. The average number of operating transformers in various substations and their percentage loadings were also studied. It was discovered that the average power supply to Government Reservation Area (GRA) was more regular and stable than that of Siluko area of Benin City.